PENGARUH CELEBRITY ENDORSER, BRAND IMAGE, KEPERCAYAAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Pembelian Merchandise Bali United Di Gianyar) - Yudha, Putu Dharma; Sudiksa, Ida Bagus (E-Jurnal Manajemen; Vol 7 No 9 (2018), 2018)
Purchasing decision is the final action of consumers based on after searching for information on the products that consumers want. The purpose of this study is to explain the influence of celebrity endorser, brand image, trust, and price to the purchase decision on Bali United merchandise in Gianyar. This research was conducted in Gianyar involving 190 respondents through purposive sampling method. Data were collected through questionnaires. Data analysis techniques used were classical assumption test, confirmatory factor analysis, multiple linear regression analysis, F test, and t test. The result of this research found that celebrity endorser, brand image, trust, and price has positive and significant effect on decision purchase of Bali United merchandise in Gianyar. So all hypotheses are accepted. The implication in management of Bali United is able to apply all indicators of research variabels. Next implication is to increase Bali United merchandise sales. keywords: celebrity endorser, brand image, trust, price, purchase decision